2006
DOI: 10.1590/s0103-84782006000400016
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de melões (Cucumis melo L. var. cantalupensis Naud.), híbrido Torreon, produzidos em hidroponia e armazenados em embalagens de polietileno

Abstract: RESUMO Este experimento teve por objetivos avaliar a permeabilidade de filmes de polietileno de diferentes espessuras e densidades ao O 2 e ao CO 2 , a composição gasosa (O 2 , CO 2 e etileno) formada no interior das embalagens e a qualidade físico-química de melões (Cucumis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In our study, a strong depletion of soluble solids content was observed in packages stored under superatmospheric O 2 levels (Table 3). A decrease in sweetness scores of fresh-cut 'Cantaloupe' melon was attributed to higher consumption rates of carbohydrates due to an increased respiratory activity (Boynton et al, 2006;Brackmann et al, 2006). However, soluble solids content could not be correlated with respiratory activity of fresh-cut melon (Fig.…”
Section: Relationship Between Respiratory Activity and Quality Paramementioning
confidence: 96%
See 1 more Smart Citation
“…In our study, a strong depletion of soluble solids content was observed in packages stored under superatmospheric O 2 levels (Table 3). A decrease in sweetness scores of fresh-cut 'Cantaloupe' melon was attributed to higher consumption rates of carbohydrates due to an increased respiratory activity (Boynton et al, 2006;Brackmann et al, 2006). However, soluble solids content could not be correlated with respiratory activity of fresh-cut melon (Fig.…”
Section: Relationship Between Respiratory Activity and Quality Paramementioning
confidence: 96%
“…A decrease in pH values could be due to lactic acid production because of the proliferation of lactic acid bacteria as it has been observed in fresh-cut cantaloupe melon (Lamikanra, Chen, Banks, & Hunter, 2000). However, some authors have related the increase in acidity with concentration of acids when fruits suffer dehydration (Brackmann et al, 2006).…”
Section: Relationship Between Respiratory Activity and Quality Paramementioning
confidence: 97%